Fighting Pandemics By Exploiting 5G, AI and Bigdata Enabled Technologies: How 5G could help us to stem Covid-19 outbreaks - Soldani, David (Journal of Telecommunications and the Digital Economy, 2020)
In context, this paper starts by referencing best practices adopted globally to counteract COVID-19, through such means as testing, tracing, diagnosing and treating infections. It then presents relevant examples demonstrating where 5G, AI and Bigdata technologies have been successfully deployed via policy measures and resulting processes to keep people safe, through physical distancing and various other arrangements to slow and contain the spread of COVID-19. Beyond this, examples of unique 5G characteristics, such as improved throughput, latency and reliability, and 5G resilient network configurations (including all layers and domains supporting standard security and related enhancements) are described in detail. This is followed by illustrating particular opportunities achievable on secure and resilient 5G systems incorporating digital spill-over capability. Beyond this consideration and responding to some unfounded concerns, the paper reaffirms that 5G will not have the negative effect on people’s health about which a few individuals have speculated. Picturing all this together, conclusions are drawn on a possible way forward in which policy makers’ focus can now advance from current Smart City concepts towards a more extensive Smart Society approach.